Relation Among Temperature, Salinity, pH and DO of Seawater Quality - Khan, Zakir Hossain (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Worldwide coastal and marine resources provide a wide range of essential ecological, economic and social benefits. Temp (OC), pH, Salinity (ppt) and DO (mg/L) measured monthly at sampling point of seawater for twelve months monitoring period in the Bay of Bengal to monitor the variation of selected parameters at six selected locations near Moheshkhali Upazila of Cox’s Bazar District. Water samples collected from a depth of 0.5m. Temperature, pH, Salinity and DO levels and variation of respective monitoring location found consistent for a twelve months monitoring period. While temperature decreased, salinity increased at all sampling locations. It was also observed that, DO decreased, while temperature increased for twelve months monitoring period. Temperature of seawater of the Bay of Bengal found in a rage of 20OC to 30OC, pH found in a range of 7.6 to 8.3, Salinity measured in a range of 13ppt to 32ppt and DO measured in a range of 6.0mg/l to 7.9mg/l.